Gestiegene finanzpolitische Unsicherheit: Zur Finanzpolitik des Bundes nach dem Urteil zum zweiten Nachtragshaushalt 2021 - Thiess Büttner (Wirtschaftsdienst, 2024)
– The paper deals with the current budget crisis in Germany, which was triggered by an attempt to increase public debt beyond the limits of the German constitution. The rejection of the Supplementary Budget 2021 of the federal government by the Constitutional Court in November 2023 requires a substantial revision of budget plans. The paper first asks why fiscal policy has moved outside the rules of the constitution. The paper then addresses the question of whether the necessary turnaround in financial policy has now been initiated. To this end, the paper explores the recent supplementary budget 2023 and the proposals for the budget 2024.
Keywords: E62; H61; H62; H63; 330; Finanzpolitik; Öffentliche Schulden; Deutschland; Finanzpolitik; Öffentliche Schulden; Deutschland